Mahmudkhoja Behbudiy's Approach to Bekhbudiyi's Cultural Autonomy Project of Turkey and the Political Governance Policy - Mukhtarov Sardorbek Saydullo ogli; Gayratova Gulzoda San'atbek qizi; Mamajonova Gulmira Dilbek qizi (International Journal on Orange Technologies, 2020)
In this article, we have tried to cover the project of Mahmudhoja Behbudi and himself, which he called "invitation", "Behbudi's project of cultural autonomy of Turkestan." We also tried to shed light on the views of Mahmudhoja Behbudi on the false promises made by the Tsarist Russia and the subsequent Soviet Russia to the Turkestans.